2011
DOI: 10.1164/rccm.201010-1679oc
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoidosis-related Mortality in the United States from 1988 to 2007

Abstract: Rationale: It has been nearly 20 years since sarcoidosis mortality was examined at the population level in the United States. Objectives: To examine mortality rates and underlying causes of death among United States decedents with sarcoidosis from [1988][1989][1990][1991][1992][1993][1994][1995][1996][1997][1998][1999][2000][2001][2002][2003][2004][2005][2006][2007]. Methods: We used data from the National Center for Health Statistics to (1) calculate age-adjusted sarcoidosis-associated mortality rates; (2) ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
193
7
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 329 publications
(222 citation statements)
references
References 17 publications
14
193
7
8
Order By: Relevance
“…The authors evaluated sarcoidosis-related mortality compared with the general population, the impact of the most prevalent sarcoidosis-related comorbid conditions, and geographical differences within France. They found that deaths were higher and at younger ages among sarcoidosis patients than among the general population, confirming previous findings from the USA [25,26]. Women died less frequently than men, but the average age at death was similar for both sexes.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…The authors evaluated sarcoidosis-related mortality compared with the general population, the impact of the most prevalent sarcoidosis-related comorbid conditions, and geographical differences within France. They found that deaths were higher and at younger ages among sarcoidosis patients than among the general population, confirming previous findings from the USA [25,26]. Women died less frequently than men, but the average age at death was similar for both sexes.…”
supporting
confidence: 78%
“…It has been estimated that 15% of the metropolitan French population is non-white (10% Northern African, 3.5% black, 1.5% Asian) [31]. In addition, an earlier study showed excess disease incidence and morbidity among Afro-Caribbean immigrants to Paris [32]; while in the USA, the highest age-adjusted sarcoidosis-related mortality rates occur among non-Hispanic black patients [25]. Taken together, race and ethnicity are likely to have an impact upon sarcoidosis mortality in France.…”
mentioning
confidence: 99%
“…Recent diagnostic and therapeutic approaches are summarized in a concise clinical review on sarcoidosis by Baughman and colleagues (49). An epidemiologic study analyzing causes of deaths in 23,679 U.S. decedents with sarcoidosis demonstrated that from 1988 to 2007, age-adjusted sarcoidosis-related mortality rates increased 50.5% in women and 30.1% in men (50). Interestingly, regardless of sex or race, mortality rates climbed most in decedents 55 years or older, and the most common cause of death was sarcoidosis itself.…”
Section: Other Dplds Sarcoidosismentioning
confidence: 99%
“…The age-adjusted mortality was 12 times higher than in white people [11], and the radiographic stages of sarcoidosis were more advanced [12]. Also, a significant increase of mortality was reported for black females aged 55 years and older [13]. 6.…”
Section: Methods C: Epidemiological Phenomena Of Sarcoidosismentioning
confidence: 99%